Effects of art in retail environments. Issue 3 (27th May 2018) - Oh, Hyunjoo; Lee, Ha Kyung; Kim, Jimin; Choo, Ho Jung
Abstract: Artworks have been introduced to retail environments outside of the art gallery and museum setting, with the assumption that art can transfer everyday consumption experiences into special and memorable ones. However, the question on the effectiveness of the placement of artwork in retail environments in influencing consumers' behaviors and experiences has not been addressed. Using the Sacred Heart sculpture by Jeff Koons, we conduct two studies to test the influence of art on an individual's behavioral intention to visit a restaurant and expected experience of food consumption. Study 1 corroborates that the effect of attitudes toward an artwork on behavioral intentions is amplified when consumers' art knowledge and levels of openness to experience are low, indicating that consumers who lack art appraisal skills are likely to be dependent on their attitude toward art. Study 2 examines the mediating roles of attitudes toward an artwork and an artist by manipulating art attractiveness and artist information as the sources of esthetic perceptions. The artist information serves as the factor boosting the effect of art attractiveness on the behavioral intention through the mediation of attitudes toward the artwork and the artist. Results show that how consumers perceive an artwork, namely artistic processing in a retail environment, is powerful in leading them to enter a store and have desirable consumption experiences. Retailers can also enhance consumer experience by selecting artworks based on target consumers' level of art knowledge and openness to experience.